2021
DOI: 10.1039/d1ra00942g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a metal–organic framework by plasma in liquid to increase reduced metal ions and enhance water stability

Abstract: Plasma in liquid provides a method for the synthesis of HKUST-1 with increased reduced metal ions and high water stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Given that film hydrophilicity is the root cause of moisture susceptibility, researchers have been devoted to the hydrophobic modification of sensitive materials. For example, the water stability of MOFs can be enhanced by directly synthesizing water-stabilized MOFs or by functionalizing their surfaces with hydrophobic agents. However, these approaches often require complicated fabrication processes with sophisticated microfabrication equipment. Alternatively, the hydrophilicity can be obtained by a thermal vapor deposition method of thin polydimethylsiloxane (PDMS) coating onto the MOF membrane, which significantly improves its water resistance while preserving the morphology of MOF nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Given that film hydrophilicity is the root cause of moisture susceptibility, researchers have been devoted to the hydrophobic modification of sensitive materials. For example, the water stability of MOFs can be enhanced by directly synthesizing water-stabilized MOFs or by functionalizing their surfaces with hydrophobic agents. However, these approaches often require complicated fabrication processes with sophisticated microfabrication equipment. Alternatively, the hydrophilicity can be obtained by a thermal vapor deposition method of thin polydimethylsiloxane (PDMS) coating onto the MOF membrane, which significantly improves its water resistance while preserving the morphology of MOF nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular applications is the chemical and biological purification of water, air and surfaces. [13][14][15][16][17] NTP has also been used for the modification and synthesis of polymers 16,18,19 and metal-organic frameworks (MOFs) [20][21][22] as well as in CO 2 conversion 3,23,24 and for a range of oxidation processes. 12,[25][26][27][28] However, several limitations such as lack of control over the plasma flux, selectivity or solvent evaporation still need to be addressed before NTP can become a mainstream synthetic technique.…”
Section: Introductionmentioning
confidence: 99%
“…20 Kanno and co-workers have stabilized M−X− M based clusters by employing a number of multifunctional ligands. 21 This approach appears to give precise and controllable M−X−M cluster units. In studies involving 2-mercaptonicotinic acid, it was established that the precise M 6 cluster (M = Cu + / Ag + ) can be stabilized both as individual units and also as an extended assembly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been demonstrated that the use of temperatures greater than 100 °C under hydro/solvothermal conditions results either in metal clusters with M–O­(H)–M linkers or extended arrangements (one-dimensional (1D), two-dimensional (2D), or three-dimensional (3D)) of M–O­(H)–M connected by organic linkers . Kanno and co-workers have stabilized M–X–M based clusters by employing a number of multifunctional ligands . This approach appears to give precise and controllable M–X–M cluster units.…”
Section: Introductionmentioning
confidence: 99%